PERANAN QUALITY OF WORK LIFE DALAM MENINGKATKAN KINERJA - Budi Gautama (Yurisprudentia: Jurnal Hukum Ekonomi, 2016)
Quality of work life is a continual management approach aimed at improving the quality of work. Understanding the quality of work life is a program that includes ways to improve the quality of their lives by creating better jobs. Various factors need to be met in creating a quality of work life programs, among others, the restructuring of work, reward systems, work environment, work participation, pride, career development, conflict resolution, communication, health, and so forth. There are three aspects of quality of work life, as follows: a) Restructuring of work, b) System benefits and c) Work environment.Performance of an employee's performance itself and the level of potential employees in their efforts to develop themselves for the benefit of companies and organizations. Performance is the result of the quality and quantity of work achieved by an employee in carrying out their duties in accordance with the responsibilities assigned to him. aspects or indicators contained in the performance among others: a) the quality of the work, b) the honesty of employees, c) initiative, d) presence, e) attitude, f) cooperation, g) the reliability, h) knowledge of the work, i) responsibilities, j) Utilization of working time